Characterization and identification of three thermophilic Bacillus strain isolated from Domas Crater, Mt. Tangkuban Perahu, Indonesia - RATU SAFITRI; DELICIA PUTRI KUSUMAWARDHANI; ANNISA ANNISA; Ruhyat Partasasmita; SINTA ASHARINA; ANI MELANI MASKOEN (Society for Indonesian Biodiversity, 2020)
Abstract. Safitri R, Kusumawardhani PD, Annisa, Partasasmita R, Asharina S, Maskoen AM. 2020. Characterization and identification of three thermophilic Bacillus strains isolated from Domas Crater, Mt. Tangkuban Perahu, Indonesia. Biodiversitas 21: 3444-3453. A community of thermophiles within the hot spring of Domas Crater, Mount Tangkuban West Java, has been cultivated and identified based on the 16S ribosomal RNA gene sequence. The hot spring has a temperature of 45°C-76 °C, pH 1-2, the isolate has been cultivated in Thermus medium at a temperature of 70 and pH 6. The three isolated strains were L61A, TS61A, and D41A identified based on the 16S ribosomal RNA gene sequence refer to the GenBank database and all of them belong to the Phylum Firmicutes, which are clustered within the taxonomic groups of Bacillus, the Bacillus, and Geobacillus genera. Nucleotide sequences were compared for homology with BLASTN search at the NCBI Web-site revealed that strains (L61A) had 99.93% similarity with Geobacillus uzenensis. TS61A strain has a 99.24% similarity with Bacillus wiedmannii. Whereas D41A has 99.79% similarity with Bacillus paramycoides. The characterization also includes the phenotypic and biochemical of strains. The bacillus genera were known as a source of thermostable enzymes, plant growth-promoting, probiotics, decomposers of various polysaccharide materials, and bioremediation.